The effects of different doses of caffeine on performance, rating of perceived exertion and pain perception in teenagers female karate athletes - Hamid Arazi; Marzieh Hoseinihaji; Ehsan Eghbali
ABSTRACT The present study set to examine the effects of different doses of caffeine on performance, rating of perceived exertion (RPE), and pain perception in female teenager athletes of karate. Ten female karate athletes (16.8±1.23 years; height 1.59±0.28 m; body-mass 57.73±8.33 kg; BMI 22.71±3.05 kg/m2) participated in the study. A double-blind, randomized, and crossover counterbalanced design was used. In three sessions (with an interval of seven days'), ten female karate athletes ingested low dose (2 mg/kg), moderate dose (5 mg/kg) caffeine, and placebo. Sixty minutes after consumption, they performed the tests as below: one repetition maximum and 60% of one repetition maximum in the leg press, explosive power test, and anaerobic RAST test. After the tests, the participants' RPE (6-20 scale) and pain perception (0-10 scale) were recorded using various categorical scales. The results showed that caffeine ingestion at moderate dose significantly reduced RPE and pain perception values compared with the placebo during muscular endurance test (P=0.0001 and P=0.039, respectively). The findings suggest that caffeine dose of 5 mg/kg body mass appears to improve RPE and pain perception in female teenager athletes of karate. The dose of 2 mg/kg body mass does not confer any additional improvement in performance.